Beyond Fast Food: The Social Appeal of McDonald’s Among Malaysian Youth - Daisy Mui Hung Kee; Dee Ning Tan; Boon Kiat Tan; Hui Qi Tan; Jia Xuan Tan (Journal of The Community Development in Asia, 2026)
This study investigates the social appeal of McDonald’s among young people by examining how social interactions, brand image, ambience, perceived enjoyment, and peer influence shape spending behavior and customer satisfaction. Based on survey data from 200 customers, our findings reveal that social interactions, perceived enjoyment, and peer influence significantly enhance spending behavior, whereas ambience and brand image show no meaningful effect. In predicting customer satisfaction, social interactions, perceived enjoyment, and spending behavior emerge as significant contributors, while ambience, brand image, and peer influence do not. Our findings demonstrate that McDonald’s functions as more than just a fast-food outlet. It serves as a social space where interpersonal connections and enjoyable experiences drive both spending and satisfaction. Our study offers practical implications for marketers and managers seeking to improve youth engagement by strengthening social experiences and enhancing enjoyment within fast-food environments